AGAMA DAN IDEOLOGI POLITIK TELA'AH RELASI AGAMA DAN NEGARA PERSPEKTIF ISLAM (DI INDONESIA) - Moh. Maksum (LP2M Universitas Ibrahimy, 2013)
It is undeniable that within this decade, Muslims are always positioned as subordinate to the interests of others, either in politics, economy, or social and cultural case. A growing speculation is that it is the impact of religion dogmatism that has affected the Muslims’ mindset and actions, so they are rather closed to the criticism against them. A solution offered is they need to open and revive the door and the spirit of ijtihad. Truly contemporary Islamic thinkers, by their Islamic political thought and constitution, could be an alternative for the contemporary Islamic political thought which its and thoughts ideas in general focused on the rejection to the caliphate system.While Islam, have the view that there is a relationship between akidah, syariah, religion and government (dawlah). Islam is not merely a spiritual treatise. Governance in Islam different from the understanding of Western thought. There are three models of paradigms to understand the relationship between religion and state. First, secular paradigm, this paradigm provides an outline disparity between religion and state. Second, integrative paradigm, in this perspective, religion and state relations is an integral and inseparable. Third, symbiotic paradigm, according to this view, the relation between religion and the state are reciprocal. It means that religion does not have to be formalized in a state institution. This article attempts to uncover the organic paradigm that explains again that religion and state into one unified whole.